The Influence of Dietary Arginine Supplementation on Blood Traits of Broiler Chickens - Al-Daraji, Hazim J.; Salih, Atta M. (Pakistan Journal of Nutrition, 2012)
A total of 300 one day old Ross 308 broiler chicks were used in this study to determine the effect of supplementing ration with different levels of arginine on productive performance of broiler chickens. The chicks were allocated for 4 treatment groups (75 chicks for each group) and each treatment was consisted of five replicates with 15 chicks each. Treatment groups were: C: control group (without any addition of arginine); T1, T2 and T3: adding arginine to the diet of broiler chickens at levels of 0.02, 0.04 and 0.06%, respectively. Two types of diets were used over the period of experiment, starter diet was used from one to 20 days of chicks’ age and then grower diet was used till the end of the experiment (46 days of age). Blood traits included in this study were total erythrocytes count (RBC), Packed Cell Volume (PCV), Hemoglobin concentration (Hb), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), total leucocytes count (WBC), hetrophil to lymphocyte ratio (H/L) and thrombocytes count (Thr.). Results indicated that adding arginine to the diet of broiler chickens (T1, T2 and T3) resulted in significant increase in RBC, PCV, Hb, MCV, MCH, MCHC, WBC and Thr. and significant decrease in H/L ratio during all periods of experiment and regarding the total means of these traits as compared with control group. In conclusion, supplementation of the broiler ration with L-arginine resulted in significant improvement with respect to blood traits included in this study. Therefore, arginine can be used as effective feed additive for enhancing physiological status of broiler chickens.